ANALISIS KELAYAKAN USAHA SEBLAK PRASMANAN DITINJAU DARI ASPEK PASAR DAN PEMASARAN SERTA ASPEK TEKNIS DAN PRODUKSI - Lestariawati, Diyah; Dio Wardana Putra; Siti Ulfatun Khasanah; Siti Badiatul Umroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the feasibility of the Seblak Netizen Prasmanan Mba Vina business which offers the concept of seblak food in the form of a buffet reviewed from two main aspects, namely market and marketing aspects and technical and production aspects. This study uses a descriptive qualitative approach, with data collection through direct observation and interviews with business activities. The results of the study indicate that Seblak Netizen Prasmanan Mba Vina has promising potential through product excellence with a buffet system, varied products, affordable prices, promotions through social media, and a strategic business location. In addition, with a strategic location, effective and efficient business layout, smart production equipment, and production processes, as well as smart production capacity, support the possibility of increasing the production capacity of the Seblak Netizen Prasmanan Mba Vina business. Based on the results of the analysis, it can be concluded that the Seblak Netizen Prasmanan Mba Vina business is considered feasible to be run and developed because it has met the feasibility indicators both in terms of market and technical production.